PKM KATEKESE TENTANG MENGHAYATI NILAI KERAJAAN ALLAH DALAM ERA DIGITAL BAGI ANGGOTA KMK. ST. MARTINUS PAROKI PERSIAPAN ST. MARINUS PU’URERE - Aurelius Fredimento; John M. Balan (LPPM Universitas Flores, 2020)
The development and the progress of media communication at the present is a fact of the knowledge and the technology development that must be accepted. It presence like the flowing water which has a fast current that brings also two influences both positive and negative that must be accounted for the members of the Catholic Students Community Of St. Martinus Ende (KMK St. Martinus Ende). Both positive and negative influences the media community like a kinetic energy or a power attraction that attract them in a tiring ambiquity. Let them walk alone without escort of a decisive compass where they should have a rightist attitude and responsible. On the point, the guidance and assistance of the church is an offering if the church will be born a generation of the future of the church that is mature and has a certain quality based on the growth and the development of acuteness and inner to determine the attitude to the development of media communication. The process of sharpening of mind and the sharpeness of the participants can be realized by giving some activities such as: awareness, deepening and even the sharpeness of the actor of media communication as an alternative of reporting work of the God Kingdom for human beings. It becomes the main moving spirit or activator for the board of KMK Of St. Martinus Ende to plan and boring about the activity of catechism. The activity rise the method of Amos. By this method, the participants are invited to build a deeply reflection that based on thein real experiences about the media communication, while keep on self opening to the God planning will come to them and give them via the commandment of God. The commandment of God come to light, inspiration, motivate, power and critics to the participants about the using of the media communication as a media of the commandment of the kingdom of God to the world that is more progress and development lately.